Strategies and process in applying participatory communication for agricultural development programmes in the Plateau State, Nigeria - Kigbu, Anna Benson (2019)
In recent times, participatory communication for development has globally been considered as an important factor in development projects. This development approach in theory is an approach which is meant to carry the people along in every stage of a development project through dialogic communication so as to enhance the success of that particular project. Even though a number of development agencies proclaim this approach (the participatory approach) as an objective, they do not fully apply this approach as they wish to. Due to the fact that a number of development projects label themselves “participatory projects” and do not fully engage in an authentic one, there is a need to understand how these development projects perceive the participatory approach in whole, and in specific, participatory communication for development. More so, the study focused on exploring how participatory communication for development is applied in terms of process and strategies by agricultural development agencies. In order to achieve the objectives of the current study, qualitative multiple case study approach was used, and semi-structured in-depth interviews were conducted among agricultural development program managers in two agricultural development agencies in Plateau State, which were selected using purposive sampling. The data obtained from the field was analysed using qualitative thematic analysis, and a rich and thick description of the studied phenomena was given. Findings of the study revealed that the two agricultural development agencies perceived participatory communication for development as a communication approach that enhances sustainability through empowerment, knowledge co-sharing and participation of farmers. The findings also revealed that in agricultural development projects dialogue and monologue are the main strategies used during development projects. Findings the strategies of participatory communication and the process involved when this communication approach is being applied in agricultural development programmes. The factors which challenge the application of participatory communication for development in agricultural development projects were revealed by the findings of the study. In a nut shell, the findings showed that the two agencies use two main strategies of participatory communication, which dialogue and monologue. However, it was observed that the use of dialogue was more prominent in the first case study, while the second one use more of monologue in its agricultural development programmes. In terms of the process, it was found that the process is a three-stage process, and the three stages include participatory needs assessment, planning stage, and implementation stage. The study concluded by suggesting that one of the main ways through which development agencies can strengthen the use of this approach, is by making conscious efforts to understand the key principles of the approach so that it can be used to facilitate the sustainability of development projects, especially agricultural development projects.